Desempenho produtivo de ovelhas em pastagens consorciadas e monocultivo de capim tamani - ROCHA, Michel Oliveira (2023)
A completely randomized design was used with three treatments: monoculture of Tamani, Tamani+Feijão Guandu and Tamani+Estilosantes, with six repetitions, with the experiment being repeated in two years of evaluation. The productive and structural characteristics of Tamani grass in monoculture and in intercrops and legumes. The consortia were superior (P<0.05%), highlighting the consortium with Estilosantes for the following variables: total forage production 7,287.43 kg ha -1 and 2,127.41 kg ha-1 ; leaf production 6,446.21 kg ha-1 and 1,625.04 kg ha-1 ; tiller population density 379.63 and 378.56 tillers m-2 ; 46.40 cm and 33, 70 cm in height respectively before and after grazing. There was a difference (P<0.05%) in legumes for leaf production (266.44 kg ha) and production of dead material (59.40 kg ha) for Estilosantes, with the highest height observed for Guandu Beans with (108.48 cm) in 2021. In the evaluation for these variables in 2022, there was a difference significant (P<0.05%) for monoculture and consortium with Estilosantes in 2022 for total forage production in pre-grazing with averages of 4,514.44 kg ha-1 in 1,566.22 kg ha-1 and for monoculture and Tamani+Estilosantes for leaf production 1,067.06 kg ha-1 and 1,024.43 kg ha-1 . There was only the persistence of Estilosantes in the consortiums in 2022. The consortium with Estilosantes is recommended as it positively influenced the structural and productive characteristics over the years in Tamani grass, in addition to have greater production and persistence compared to legumes.As for the composition bromatology, animal behavior and performance of sheep on Tamani grass and in consortium with legumes in 2021 and 2022, there was superiority (P<0.05) for the dry matter content with emphasis on the consortium with Guandu Beans with 52.43% in 2021 and consortium with Estilosantes 51.62% and Feijão Guandu and 49.12% in 2022. There was difference (P<0.05) of crude protein in 2021 for the consortium with Estilosantes with grades of 25% and monoculture in 2022 with an average of 13.42%. As for legumes, Guandu beans had the highest crude protein content 23.15%, neutral detergent fiber 58.74% and fiber and acid detergent 41.72%. In 2022 for behavior assessment animal in the year 2021 there was a difference (P<0.05) for the rumination time for the intercropping with Estilosantes 1.08 hours, time in the trough and time in the water fountain for the consortium with Guandu with 0.05 hours and 0.13 hours respectively. In the year 2022 there was superiority (P<0.05%) for the time in the drinking fountain for the consortium with Styling 0.19 hours and time in the trough 0.32 hours. There was an effect (P>0.05) for systemsand occupancy days with the best system between system x occupancy days with 216.36 100 bites per hour at the entrance and 222.5 bites per hour at the exit to Estilosantes and monoculture respectively. There was a difference (P<0.05) in the final weight of the sheep in 2021, being the monoculture with the highest weight of 28.01 kg. The consortium with Estilosantes was the most recommended as it presented the best characteristics in terms of composition chemistry, in addition to the consortium due to its nutritional characteristics influencing the sheep behavior, and animal performance in a positive way.